Upaya Meningkatkan Keaktifan Belajar Siswa Kelas I Dengan Media Pembelajaran Kahoot pada Materi Membandingkan Bilangan di UPTD SD Negeri Gili Barat Kamal - Sri Mei Astutik; Kusmiyati Kusmiyati (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to improve the learning engagement of first-grade students at UPTD SD Negeri Gili Barat, Kamal District, by using Kahoot as a learning media for the topic of comparing numbers. Student engagement is a key factor in achieving optimal learning outcomes, especially at the elementary school level. The method used in this study is a quasi-experiment, involving 20 students as the subjects of the research. Data were collected through observation sheets and questionnaires designed to measure the level of student engagement and motivation during the learning process. The results of the study show a significant improvement in student engagement, where the average engagement rate before the use of Kahoot was 60%, and after the application of this media, it increased to 85%. Additionally, 90% of the students reported that they felt happy and motivated when using Kahoot. This study recommends that teachers consider using educational technology such as Kahoot in basic education to enhance student engagement and learning outcomes.